PENERIMAAN ORANGTUA TERHADAP ANAK DENGAN AUTISME DI PUSAT LAYANAN AUTIS (PLA) DAERAH ISTIMEWA YOGYAKARTA - Deby Zulkarnain Rahadian Syah; Puji Sutarjo; Inna Riescananda (MEDIA ILMU KESEHATAN, 2016)
Background: Autism is a developmental disorder in children that affects their social and imaginative lifes. Parents’ acceptance on their children’s autism will have impact on how they treat their children. Objective: The aim of this study was to determine the parental acceptance of children with autism in the Autism Services Center (ASC), Yogyakarta. Methods: This study was a qualitative research with a phenomenological approach. The data collection was conducted by in-depth interviews with three informans. Results: All the informants accepted their children’s conditions, after getting information about autism. Acceptance of parents indicated their satisfaction with the children’s talent. Parents provide facilities to support the children's talents. In addition, the acceptance of parents indicated by the acceptance of the cildren’s limitations. Conclusion: Participants accepted their children’s conditions, talents and limitations. Keywords: Autism, Parental Acceptance.